Optimization of the regularization of the solution of the plate vibration problem - Fargana, A.; Rakhimov, Abdumalik; Khan, Ahsan Ali; Hassan, Torla (Research India Publications, 2018)
In this paper optimization of the regularization of the Fourier series in case of the plate vibration problem studied and the regularization of the series solutions at a fixed point of the plate studied at initial time and critical index